MOTIF PENGUSAHA MUSLIM BISNIS KULINER PERSPEKTIF ALFRED SCHUTZ; STUDI KASUS LUBNA CAKE & CAFE - Sismanto, Sismanto; Siswanto, Siswanto; Djalaluddin, Ahmad; Andriani, Sri; Rikza, Abdullah (Ekonomi Syariah STAI Sangatta Kutai Timur, 2024)
This study aims to analyze the motives of Muslim entrepreneurs in implementing mujāhadah (spiritual struggle) in their culinary business practices, using Alfred Schutz's phenomenological perspective. The study employs a qualitative approach with a case study design, focusing on Lubna Cake & Cafe in East Kutai. Data were collected through in-depth interviews, direct observation, and document analysis to explore the